Perceptions of Personal Safety Among Lower-Income Relationship Education Participants: A Grounded Theory Study. Issue 4 (1st October 2016) - Harris, Steven M.; Porter, Rob; Whiting, Jason B.; Brown, Matt; Rappleyea, Damon L.; Crabtree, Sarah A.
ABSTRACT: The federal government has fiscally supported relationship education (RE) for lower-income citizens. However, concerns exist that this particular population may be at increased risk for intimate partner violence (IPV), and some are concerned that government endorsement of RE could encourage women to stay in unsafe and violent relationships. Research examining the relationship between RE and IPV is limited. Using grounded theory, the researchers sought to answer the question: How does participation in RE impact participants' perceptions of safety in their intimate relationships? Researchers developed a theoretical model suggesting that through the course of RE, participants are exposed to both curriculum and group processes that help increase their awareness of themselves, their partner, and their relational processes, which contributes to increased feelings of connection and general safety within the relationship.